Copper(II)–cerium(III) 15-metallacrown-5 based on glycinehydroxamic acid as a new precursor for heterobimetallic composite materials on carbon nanotubes. (16th August 2016) - Kremlev, Kirill V.; Samsonov, Maxim A.; Zabrodina, Galina S.; Arapova, Alla V.; Yunin, Pavel A.; Tatarsky, Dmitry A.; Plyusnin, Pavel E.; Katkova, Marina A.; Ketkov, Sergey Yu.
Graphical abstract: The cerium–copper 15-metallacrown-5 derivative Ce(H2 O)4 [15MCCuGlyha -5]Cl3 has been prepared and employed as a single-source precursor for Cu2 O/CeO2 /MWCNT nanocomposites. Abstract: A new water-soluble polynuclear metallamacrocyclic complex, Ce(H2 O)4 [15MCCuGlyha -5]Cl3 (1 ), has been prepared under ambient conditions from copper(II) acetate and cerium(III) chloride in water, using glycinehydroxamic acid as a ligand. According to the X-ray diffraction study, crystals of1 belong to the triclinic space group P 1 ¯, similar to other 15MC-5 metallacrowns. The Ce 3+ ion is coordinated by five oxygen atoms of the MC ring in the equatorial plane and four oxygen atoms of the water molecules in apical positions. Simultaneous thermogravimetric, differential scanning calorimetric and mass spectrometric analyses (TG–DSC–MS) reveal the decomposition of complex1 with a sharp exothermal peak at ca. 200 °C. The complex has, therefore, potential application as a single-source precursor for the low-temperature growth of nanostructured cerium–copper mixed oxides under hydrothermal conditions.